Protractedness? A Driver to Sexual and Gender-Based Violence (SGBV) among Refugees in Nakivale Refugee Settlement, Southwestern Uganda - Cleophas Karooma; Clementia Murembe Neema; Eria Serwajja; Veronica Nakijoba; Sophie Withaeckx; Gily Coene (Afriche e Orienti, 2022)
This qualitative study investigates the linkage between protractedness and Sexual and Gender-Based Violence (SGBV) in Nakivale Refugee settlement. Uganda’s refugee settlements are characterized by protracted refugees due to prolonged conflicts among its neighbors and the inability to find a lasting solution for the refugees. In these settlements, SGBV is widespread yet remains a silent affliction, among women and girls, as well as men and boys, who are at an increased risk of multiple forms of SGBV as a result protractedness. The paper argues that protractedness has aggravated the challenge of SGBV, as it has created new forms of violence and exacerbated existing ones. The findings indicate that protractedness has become a big driver to SGBV, as it increases the vulnerability of women and men to the challenge of SGBV. Men as well as women perpetrate SGBV. Some refugees are reluctant to report for fear of social exclusion and some survivors and their families still conceal their SGBV experiences. While, several interventions including health, legal, psycho-social counselling, safety and security, and economic empowerment were reported to have reduced a challenge of SGBV, SGBV still exists due to frustration from long stay
Keywords: Sexual and Gender-Based Violence (SGBV); Protracted Refugees; Protractedness; Nakivale Refugee Settlement